Perilaku Cutting dalam Perspektif Psikologi Islam - Aziz, Akbar Nur; Rahmatullah, Azam Syukur (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
The purpose of this paper was to find out how Islamic psychology views cutting behavior and how to overcome cutting behavior according to Islamic Psychology. This research was a literature review with a descriptive qualitative approach. The data collection technique was done by searching for sources of books and journal articles with the theme of mental health on Google Scholar and Scopus. The data analysis was carried out by collecting data, breaking them down into units, synthesizing, compiling patterns and drawing conclusions. The results of the study showed that cutting behavior is a form of human reaction that experiences problems, anxiety, or bad experiences from someone so that they feel guilty or disappointed with themselves. Cutting means clawing, cutting, or slashing limbs. Cutting behavior seen from the perspective of Islamic Psychology is an act that is forbidden because the impact can kill lives. The touching heart method with Islamic counseling, Qalbun Healing with a Sufism approach, namely dhikr accompanied by prayer readings can be alternatives in healing from cutting behavior.